The Establishment And Development Of Diplomatic Relations And Partnership Between European Union And The Philippines - Dan Vataman (CV. AFDIFAL MAJU BERKAH, 2023)
Considering the dynamic developments in the EU-Philippines partnership, the main purpose of this study is to clarify some aspects regarding the establishment of bilateral relations and also to highlight the concerted efforts made by both sides to become reliable partners. In this connection, the research undertaken has been focused on efforts made to negotiate and adopt the final form of the EU-Philippines Framework Agreement on Partnership and Cooperation, a document which provides an enhanced legal framework. In order to achieve this objective, qualitative and quantitative research methods were used. A special attention was also paid to the negotiations for the future EU-Philippines Free Trade Agreement, a legal act which would aid the two parties in achieving mutually beneficial economic goals. To realise this proposed aim, inductive reasoning conducted the research from the specific of the EU-Philippines partnership to the general situations, while deductive reasoning allowed to make an inference by going from general premises to specific conclusions. The research highlighted the Romania-Philippines friendship and the support provided by Romania as an EU Member State in the process of strengthening EU-Philippines relations. To achieve this goal, comparative and analytical methods were used for interpreting information and reach relevant conclusions.